STRATIFIKASI SOSIAL DALAM ISLAM: TINJAUAN TERHADAP STATUS SOSIAL DALAM KELUARGA DAN MASYARAKAT - Syamsuriah Syamsuriah (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
What makes people differ from the others before Allah is just a religious piety (taqwa). In sociological perspective, Muslim people also talk about someone's social status, like the different status of the Prophet and the Messenger on the Earth, as well as status of khalifah and president as the ruler. So, stratification is known in Islam as the Quran elucidated about the noble pious men on the Earth. The emergence of social stratification in society begins since the early existence of man, and it differs from one community to the other in different places, customs, traditions, and norms that are practiced in each community.